Discussion on 'From Pan-African transpression to Cadomian transtension at the West African margin: new U–Pb zircon ages from the Eastern Saghro Inlier (Anti-Atlas, Morocco)' by Errami et al. 2020 (SP503, 209–233). Issue 4 (2021) - Ikenne, Moha; Bekker, Andrey; ,; Ernst, Richard E.; Youbi, Nasrreddine; Lahna, Abdelhak Ait; Söderlund, Ulf; Tassinari, Colombo C. G.; Ousbih, Mehdi; Boumehdi, Moulay Ahmed; Bensalah, Mohamed K.
No abstract available